2008
DOI: 10.1111/j.1468-036x.2007.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Restructuring and Bondholder Wealth

Abstract: "This paper provides an overview of existing research on how corporate restructuring affects bondholder wealth. Restructuring is defined as any transaction which affects the firm's riskiness by changing its underlying capital structure. Thus, it reaches well beyond asset restructuring and includes transactions such as leveraged buyouts, security issues and exchanges, and the issuance of stock options. We identify significant gaps in the literature, emphasize the potential differences in bond performance betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 122 publications
1
18
0
6
Order By: Relevance
“…Alternatively, this may be achieved via shareholder activism such as proxy proposals (Cziraki et al, 2010;Renneboog and Szilagyi, 2008), pressure on the management by shareholder coalitions (Becht et al, 2010;Crespi and Renneboog, 2010), and the threat of a disciplinary takeover (Franks et al, 2001). However, shareholder monitoring is costly and only generates a sufficient payoff if the monitoring shareholder has a large enough share stake.…”
Section: Compensation and Incentivesmentioning
confidence: 98%
“…Alternatively, this may be achieved via shareholder activism such as proxy proposals (Cziraki et al, 2010;Renneboog and Szilagyi, 2008), pressure on the management by shareholder coalitions (Becht et al, 2010;Crespi and Renneboog, 2010), and the threat of a disciplinary takeover (Franks et al, 2001). However, shareholder monitoring is costly and only generates a sufficient payoff if the monitoring shareholder has a large enough share stake.…”
Section: Compensation and Incentivesmentioning
confidence: 98%
“…In their study, they examined 4.000 firms from 33 different countries and indicated that companies operating in countries with stronger legal protection, pay higher dividends. Renneboog and Szilagyi (2006) state that the Dutch companies with strong shareholders demand higher dividend payouts. Michaely and Roberts (2006) emphasize that strong corporate governance encourages higher and more consistent dividend payouts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shleifer and Summers (1988) argue that new investors in hostile takeovers may break the implicit contracts between the firm and its stakeholders (in particular, the employees by reducing employment and wages). Nevertheless, Weston et al (1998) note that such hostility against employees is not observed in PTP transactions, although there is some evidence of falls in employment and wages after adjustment for industry effects in both the US and the UK (Kaplan 7 For a detailed overview of this literature on bond wealth effects: see Renneboog and Szilagyi (2008). In a recent paper on the more general context of takeovers, Renneboog, Szilagyi, and Vansteenkiste (2017) show that bond returns respond to cross-border acquisitions where the target and bidding firms are located in countries with different creditor protection and claims enforcement.…”
Section: Wealth Transfers From Other Stakeholdersmentioning
confidence: 99%